Inorganic Membranes for Energy and Environmental Applications - Bose, Arun C. (Springer New York : Imprint: Springer, 2009)
The study of inorganic membrane materials and processes is a rapidly expanding research interest area. This is due to the recognition that research results in recent years have created membrane-based technology modules with the potential to improve the cost, efficiency, and environmental performances of energy production systems beyond current benchmarks. This book documents progress in inorganic membranes, especially in advanced materials and novel separation concepts, with applications for cost-effective and environmentally-progressive energy production solutions. The book chapters address inorganic membranes on three transport mechanisms, i.e., mixed ion-electron conduction, solution-atomic diffusion, and size exclusion filtration of the permeate phase. Inorganic Membranes for Energy and Environmental Applications provides a single source reference for researchers contemplating continued advancement of inorganic membrane technology to novel capabilities for applications to future energy and fuel production systems and potentially, technology-based responses to address greenhouse gas emission concerns. This book is meant for scientists, engineers, industry R&D personnel, and graduate students engaged in the development, engineering scale-up, and applications of inorganic membrane materials and processes, and non-technical management staff delegated with programmatic and resource allocation decision authorities who need to know about state-of-the-art current inorganic membrane technology.